FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA - Lesmana, Daniel; Santioso, Linda (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research was to analyze the influence of firm size, firm age, leverage, profitability, and audit quality on the dependent variable, namely earnings management. The research object used were manufacturing companies listed on Indonesia Stock Exchange from 2018 to 2021. The sampling method that used in this study is purposive sampling method. There are used 70 companies as the final sample I used in the study. Data analyzed using multiple regression method. Modified Jones model approach was employed in this research. The result of this study indicated that firm size and profitability have a significant negative effect on earnings management. Firm age and leverage have a significant positive effect on earnings management. Audit quality has insignificant positive effect on earnings management.